MAHABBAH DALAM PERSEPEKTIF RABI'AH AL-ADAWIYAH - Lia Anggraeni; Ananda Nurzahra Wahidah; Maftuh Ajmain (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Mahabbah or Divine love is an important aspect of Sufism which emphasizes the spiritual relationship between humans and Allah. Rabi'ah al-Adawiyah, a Sufi woman from the 8th century, developed the concept of sincere mahabbah, namely love that is not based on the desire for reward or fear of punishment. His thinking brought a change from a transactional Sufistic approach to love that is pure and completely directed towards Allah. This research aims to explore the concept of mahabbah according to Rabi'ah al-Adawiyah, its impact on spiritual life, and its relevance in Islamic practice in the modern era. The method used is library research in which the researcher collects sources using a qualitative approach because the data produced is in the form of words or descriptions. The results of the study show that mahabbah according to Rabi'ah emphasizes an attitude of total surrender to Allah without expecting anything in return. This concept remains relevant in forming individual piety that does not only focus on rituals, but also reflects sincerity in worship and in living daily life.